Diathermy versus Scalpel for Abdominal Incisions in Caesarian Section (Central Medical College Journal, 2025)
Objective: To compare the mean incision time, blood loss and post-operative pain with diathermy verses scalpel in caesarian sections for abdominal incisions. Methods: This is a prospective randomized study was conducted in the Department of Gynaecology & Obstetrics, of a tertiary hospital in Bangladesh from January 2022 to December 2022 for a period of 12 months. Total 436 women with singleton pregnancy of gestational age 37-41 weeks undergoing cesarean section of 20-40 years of age were selected and randomly divided into two groups of 218 women in each. Patients were randomized to have either scalpel or diathermy incisions. The duration used in making the skin incision was noted. Blood loss, postoperative pain, duration of wound healing and the occurrence of surgical site infection were also noted. Results: The mode of presentation was predominantly elective. The incision time was shorter in the Group A (Diathermy group) 3.7 ± 1.3 minutes while in Group B (Scalpel group) was 5.4 ± 1.7 minutes (P < 0.001). The blood loss was less with the diathermy compared to the scalpel (4.45 ± 2.27 ml vs. 7.32 ± 3.47ml, P < 0.001). The cumulative numerical rating scale score for pain was 12.75 (standard deviation [SD] 6.07) and 17.65 (SD 9.59) in the diathermy and scalpel groups respectively (P < 0.001). There was no statistically significant difference in wound infection and wound closure (epithelialization time) (P = 0.207).Conclusions: This study concluded that the diathermy incision is better than scalpel skin incisions in terms of incision time, blood loss and post-operative pain.Central Medical College Journal Vol 9 No 1 January 2025 Page: 18-22